State of State and Cooperative Retail Trade in Sverdlovsk Region in 1940s - V. N. Mamyachenkov; V. S. Plokhotnikov (Научный диалог, 2019)
The article is devoted to the problem almost not developed in regional historiography. The purpose of its writing was to study the state of retail trade of the Sverdlovsk region in one of the most difficult periods in the history of the USSR - during the Great Patriotic war and the first few years after its end. The base of the study was archival materials unpublished to date. It is stated that trade is an integral part of the reproduction process. It is stated that the inattention of domestic historians and economists to the problems of the development of trade services was caused by the priority in the scientific research of Soviet social scientists in such areas of the economy as industry, industrial construction and agriculture. It is declared that trade in the Soviet Union under the domination of the planning and distribution economy has never enjoyed the attention of the authorities, and therefore the lag in its development in comparison with civilized standards was impressive. It is argued that the main negative consequence of the war for the retail trade of the Middle Urals was only a slight reduction in its turnover. The thesis is put forward that in the war years the provision of food to the population was entrusted to the departments of working supply and catering enterprises. It is noted that during the war the population of the region engaged in self-sufficiency actively as never before. It is concluded that in the situation of total commodity deficit, the actual absence of a normally organized market and the complete arbitrariness of the authorities, the sphere of trade was doomed to the role of a hostage of an entirely state-owned economy of the planning and distribution type.